Ultrahigh-Sensitivity Liquid Refractive Index Sensor With Two-Mode Interferometer Embedded in Each Arm of Mach-Zehnder Interferometer - Zhang, Yinglu; Wang, Liwen; Yao, Hao; Deng, Jiayao; Wu, Jieyun; Zhao, Zhiying; Chen, Kaixin (Journal of lightwave technology, 2025)
In this paper, we propose and demonstrate experimentally an ultrahigh-sensitivity liquid refractive index (RI) sensor by embedding a two-mode interferometer (TMI) in the arms of a Mach-Zehnder interferometer (MZI) to exploit the Vernier effect. For comparison, we meticulously designed, fabricated, and tested two categories of sensors with four distinct configurations, including standalone rectangular and ridge waveguide TMI sensors, as well as the MZI sensors with these two types of TMI embedded into the arms of the MZIs. The experimental results show that the fabricated MZI sensors embedded with rectangular and ridge waveguide TMIs achieve the maximum sensitivities of 20264 and 51871 nm/RIU, respectively. While the fabricated standalone rectangular and ridge waveguide TMI sensors with almost identical dimensions achieve the maximum sensitivities of 5027 and 8540 nm/RIU, respectively. These experimental results confirm that integration of the VE and the ridge TMI into MZI configuration can significantly enhance sensor sensitivity.